Faktor Risiko Keluhan Musculoskeletal Disorders Bagian Ekstremitas Atas pada Pekerja Pengolahan Karet di PTPN XII Kebun Renteng - Ria Istiqomah (Pustaka Kesehatan, 2022)
International Labor Organization (ILO) reported 2.78 million people died from occupational diseases and accidents every year in 2018. One of the occupational diseases is musculoskeletal complaints (ILO 2017:10), the complaints could be mild to severe. Musculoskeletal complaints are divided into several, one of which is the upper extremities. Musculoskeletal in the whole body or in part can be experienced by various parties, one of which is workers in various industrial sectors such as in the Rubber Processing Factory. The purpose of this study was to describe the risk factors for complaints of upper extremity musculoskeletal disorders in rubber processing workers at PTPN XII Kebun Renteng. This study is a descriptive study, using primary data through interviews with all 27 workers and observations were made using the Job strain Index (JSI) questionnaire and the level of pain complaints using the Nordic Rating Scale (NRS). The results of the study mostly experienced moderate levels of pain. Individual characteristics that influence are age, years of service, and exercise habits. The influencing factor of work is the length of work. The advice given to researchers is to hold regular health checks for workers, including checking for MSDs complaints, especially for at-risk groups, namely workers aged 35 years and working years > 10 years.